2018
DOI: 10.29024/aogh.910
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Organic Compounds in Air: Sources, Distribution, Exposure and Associated Illnesses in Children

Abstract: Background:Toxic volatile organic compounds (VOC), like benzene, toluene, ethylbenzene and xylenes (BTEX), are atmospheric pollutants representing a threat to human health. They are released into the environment from mobile sources in urban settings, but newly polluted areas are gaining importance in countries where accelerated industrialization is taking place in suburban or rural settings.Methods:The review includes studies done in Mexico and Latin-America and countries considered to have emerging economies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
122
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(123 citation statements)
references
References 47 publications
1
122
0
Order By: Relevance
“…There are also higher levels of PAHs and VOCs [18] in wildfire smoke compared to ambient pollution. Many of these are known to be carcinogenic, including benzo(a) pyrene, formaldehyde, and benzene [27,36,37]. Some research has also linked exposure to VOCs with wheezing [36].…”
Section: Composition Of Wildfire Smoke and Potential Health Effects Omentioning
confidence: 99%
See 1 more Smart Citation
“…There are also higher levels of PAHs and VOCs [18] in wildfire smoke compared to ambient pollution. Many of these are known to be carcinogenic, including benzo(a) pyrene, formaldehyde, and benzene [27,36,37]. Some research has also linked exposure to VOCs with wheezing [36].…”
Section: Composition Of Wildfire Smoke and Potential Health Effects Omentioning
confidence: 99%
“…Many of these are known to be carcinogenic, including benzo(a) pyrene, formaldehyde, and benzene [27,36,37]. Some research has also linked exposure to VOCs with wheezing [36]. Given that wildfire exposures are recurring, these exposures could have important implications for lifetime cancer risk.…”
Section: Composition Of Wildfire Smoke and Potential Health Effects Omentioning
confidence: 99%
“…Some previous studies found indoor concentrations were much higher than outdoor concentrations for most VOCs [ 36 ]. Nevertheless, indoor exposure to VOCs may be more dependent on outdoor pollutants in temperate and warm latitudes, where building construction is generally less tight and doors and windows are opened more frequently, allowing for air exchange [ 37 , 38 ]. In fact, our data show that approximately 70% of the participants opened the bedroom window once or twice a day.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their toxicological and/or carcinogenic properties, some volatile organic compounds (VOCs), aromatic hydrocarbons and carbonyls have increasingly gained attention in the international scientific community dealing with public health issues [1][2][3]. In the last decades, researchers, interested in non-communicable diseases and prevention, focused on the interaction between the aforementioned chemicals and human health, especially in preventive terms [4][5][6].…”
Section: Introductionmentioning
confidence: 99%